ANALYSIS INHIBITING FACTOR OF STUDENTS COMMUNICATION SKILL THROUGH IMPLEMENTATION OF NHT ON COLLOID MATERIAL - Rahmatulloh Rahmatulloh; Putri Novitasari; Zilla A Ukrima; Muchlis Muchlis (JCER (Journal of Chemistry Education Research), 2017)
This study was aimed to know the inhibiting factor of student communication skill in colloid material with application of Numbered Head Together model. The method of this research is descriptive quantitative and target are student of class XI IPA 2 SMAN Wonoayu Sidoarjo and XI IPA 5 SMA Al-Islam Krian with amount of 39 and 45 students. Result of this researchwas found that 41.03% of students of IPA 2 SMAN Wonoayu and 42.2% of students of XI IPA 5 SMA AL Islam Krian included communication delay. The results of data analysis showed that in XI IPA 2 SMAN Wonoayu Sidoarjo as much as 75% of student experience communication delays on ecological and psychological factors; 43.7% by the messaging and semantic factors. While in XI IPA 5 SMA Al Islam Krian 73.7% by psychological factors; 68% by ecological factors; 47.4% by messenger factors, and 42.1% by receiver and semantic factors.